Prevention first vs. cap-and-trade policies in an agent-based integrated assessment model with GHG emissions permits - Lilit Popoyan; Alessandro Sapio (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2023)
In this work, we ask whether tradable emissions permits, based on the cap-and-trade principle, provide better climate change and economic projections than alternative regulations for GHG emissions, such as operational permits which are commonly used to mitigate non-GHG emissions (prevention first principle). Towards this goal, we simulate climate and the economy through a new version of the Dystopian Schumpeter meeting Keynes (DSK) model, extended to include an emission trading system (ETS) and operational permit systems. We show that climatic and economic projections in an ETS scenario need not be superior to those in an operational permit scenario. Which system delivers more encouraging projections on temperature anomalies, the green transition, and economic dynamics depends on institutional details, such as the set of firms for which permits are mandatory; the regulatory requirement of corrective measures; the magnitude of penalties; the stringency of the ETS. An ETS with a declining number of permits emerges as the best-performing system in terms of macroeconomic, microeconomic, and climate outcomes. A system of operational permits mandatory only for large firms (centralised permits) ranks as the second-best system, provided that the regulator imposes corrective measures regarding R&D expenses and machinery replacement.
Keywords: C63; Q40; Q50; Q54; 330; Climate change; Environmental permits; Emissions trading system; Polluter pays principle; Agent-based models; Macro-economic dynamics